2022
DOI: 10.1021/acsomega.2c00149
|View full text |Cite
|
Sign up to set email alerts
|

Simple Preparation of Photoluminescent and Color-Tunable Polyester Resin Blended with Alkaline-Earth-Activated Aluminate Nanoparticles

Abstract: A simple inorganic/organic nanocomposite was used to generate long-lasting phosphorescent pebbles for easy commercial manufacturing of smart products. An organic/inorganic nanocomposite was made from low-molecular-weight unsaturated polyester and rare-earth-activated strontium aluminum oxide nanoparticles doped with europium and dysprosium. The polyester resin was mixed with phosphorescent strontium aluminate oxide nanoparticles and methylethyl ketone peroxide as a cross-linking agent to create a viscous mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The detection limit of XRF has been typically reported at 10 ppm. [ 35 ] Therefore, partial determination of the nacre‐like chemical composition was reported by XRF (Table 2). Accordingly, Sr and Al were identified by XRF in all luminous nacre‐like coatings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection limit of XRF has been typically reported at 10 ppm. [ 35 ] Therefore, partial determination of the nacre‐like chemical composition was reported by XRF (Table 2). Accordingly, Sr and Al were identified by XRF in all luminous nacre‐like coatings.…”
Section: Resultsmentioning
confidence: 99%
“…Both Commission Internationale de L'éclairage (CIE) Laboratory and colour strength ( K/S ) parameters were analyzed. [ 35 ] The CIE Laboratory represents colour as 3D numerical coordinates; where L* is brightness from black(0) to white(100), a* is the range of colours from red (+a*) to green (−a*), and b* is the range of colours from yellow (+b*) to blue (−b*). Before and after illumination with UV light, photographs of luminescent nacre‐like coats were captured using a Canon A710IS instrument.…”
Section: Methodsmentioning
confidence: 99%
“…The photoluminescent films displayed virtually similar emission characteristics to those with the LdA powder. [ 44,59 ]…”
Section: Resultsmentioning
confidence: 99%
“…The 4f 6 5D 1 ↔4f 7 transition of europium (II) ions was responsible for the fluorescence of LdA. [ 57–59 ] Neither europium (III) nor dysprosium (III) showed any typical fluorescence peaks to demonstrate a full conversion of Eu(III) into Eu(II). This indicated that dysprosium (III) absorbed light that then transferred to Eu(II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation